Upconversion‐Luminescent Core/Mesoporous‐Silica‐Shell‐Structured β‐NaYF4:Yb3+, Er3+@SiO2@mSiO2 Composite Nanospheres: Fabrication and Drug‐Storage/Release Properties. Issue 11 (24th February 2014) - Liu, Bei; Li, Chunxia; Yang, Dongmei; Hou, Zhiyao; Ma, Ping'an; Cheng, Ziyong; Lian, Hongzhou; Huang, Shanshan; Lin, Jun
Abstract: We present the fabrication, upconversion‐luminescence cell imaging, and drug‐storage/release properties of upconversion‐luminescent core/mesoporous‐silica‐shell‐structured β‐NaYF4 :Yb 3+, Er 3+ @SiO2 @mSiO2 composite nanospheres with a size of 80 nm. The biocompatibility test on L929 fibroblast cells using a 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay reveals the low cytotoxicity of the system. The drug‐storage and in vitro release tests indicate that these multifunctional nanomaterials have controlled drug‐loading and ‐release properties for ibuprofen (IBU). Moreover, the upconversion (UC) emission intensity of IBU‐β‐NaYF4 :Yb 3+, Er 3+ @SiO2 @mSiO2 composite nanospheres increases gradually along with the released amount of IBU. Additionally, upconversion luminescence images of β‐NaYF4 :Yb 3+, Er 3+ @SiO2 @mSiO2 uptaken by cells show clear green emission under 980 nm infrared laser excitation. These findings make these material promising for applications in the bioimaging, drug delivery, and disease therapy fields on the basis of its upconversion‐luminescent and mesoporous properties. Abstract : Biocompatibility in vitro, upconversion luminescence imaging, and capability of loading drug of multifunctional β‐NaYF4 :Yb 3+, Er 3+ @SiO2 @mSiO2 nanospheres were investigated.